The effect of picture and picture learning model on learning outcomes of junior high school madani makassar students - Muh Sri Yusal; Irnayanti Bahar; Bernadina Namul (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2022)
The picture and picture learning model is a learning strategy through the use of image media as learning media which are paired and sequenced logically. This learning model involves students to participate in learning activities that are innovative, creative, and fun. In addition, the picture and picture learning model is to organize the learning experience so that it can be used as a reference or guide for learning designers and teachers in planning teaching and learning activities. This research is an experimental and non PTK research. The data from this study were analyzed through descriptive statistical analysis and independent T-test which were first carried out by the process of normalization and homogenization of data. This study aims to examine the effect of the picture and picture learning model in improving learning outcomes at Madani Junior High School Makassar. The results showed that the picture and picture learning model had a significant influence on the learning outcomes of class VII Junior High School Madani Makassar. This learning model has proven to be effective in providing opportunities for students to work together with fellow students through structured, group tasks, so that open interactions and effective interdependence relationships occur among various group members.